The contribution of gully erosion to total sediment production in a small watershed in Southwest China. (4th May 2018) - Zhang, Xiyu; Fan, Jianrong; Liu, Qing; Xiong, Donghong
Abstract: Determining the contribution of gully erosion to the total sediment yield is important for enhancing decision-making regarding sediment abatement and soil conservation measures. The dry-hot valley region of the Jinsha River is one of the most intensive areas of gully erosion in China. However, the contribution of gully erosion to total sediment production in this region is unclear. Instead of using the source tracing technique commonly employed in other studies, this study provides a method of rapidly reconstructing historical sediment yields based on the properties of sediment that accumulated in an undrained pond at a small gully watershed outlet. We produced a three-dimensional model in geographical information system software to calculate the volume of each layer of accumulated pond deposits from 2006 to 2011. Moreover, we estimated sheet erosion amounts using the Universal Soil Loss Equation. The results showed that sheet erosion accounted for between 14.28 and 23.39% of the total sediment yield in the watershed in the case that the sediment delivery ratio was 100%. Therefore, gully erosion is the major source of total soil loss in this area, and effective soil measures of gully erosion mitigation are crucial for managing the sediment yield.